Insight Into Theoretical and Applied Informatics : Introduction to Information Technologies and Computer Science - Andrzej Yatsko; Walery Suslow (De Gruyter Open Poland, 2015)
The book is addressed to young people interested in computer technologies and computer science. The objective of this book is to provide the reader with all the necessary elements to get him or her started in the modern field of informatics and to allow him or her to become aware of the relationship between key areas of computer science. The book is addressed not only to future software developers, but also to all who are interested in computing in a widely understood sense. The authors also expect that some computer professionals will want to review this book to lift themselves above the daily grind and to embrace the excellence of the whole field of computer science. Unlike existing books, this one bypasses issues concerning the construction of computers and focuses only on information processing. Recognizing the importance of the human factor in information processing, the authors intend to present the theoretical foundations of computer science, software development rules, and some business aspects of informatics in non-technocratic, humanistic terms.